A Conceptual Model Of Corporate Entrepreneurship In Banking Industry - Bobby, Boon-Hui Chai; Harry, Entebang (Universiti Malaysia Sarawak (UNIMAS), 2013)
Purpose: The rapid growth of global economies, changes in technology, market competition and ever changing business environment have caused the banks to struggle for profitability, growth and performance. With the intense competition among banks in the industry, it is imperative for them to have superior performance, and the banks have attempted to implement and use various initiatives such as: TQM, BPR, SP, Six Sigma, Balanced Scorecard, ABM. However, banks being the backbone of any economy and its importance for the future growth and development of the country. Thereby, the performance of the bank is of a major concern, and with this in mind the scholars have argued that there is a strong relationship between corporate entrepreneurship (CE) and bank performance. Therefore, corporate entrepreneurship with innovative products, strategic renewal and quality services will provide the banks with competitive advantages in the organization, sustaining them in their business challenges and survival in the market place with greater performance. Design/methodology/approach: Conceptual paper Findings and implications: Conceptual paper Originality/value: The study is important to decision maker in the banking industry